Racionalidades e organizações do “terceiro setor”: uma análise da tensão entre racionalidade instrumental e substantiva a partir do discurso de trabalhadores do Instituto Terra - Marchi, Janaina (2017)
This work takes as its starting point studies that focus on the analysis of the instrumental and substantive aspects of rationality in organizations, more specifically in "third sector" organizations. The observation of the existence of these manifestations would eventually create spaces of tension in these environments, contributing to the unleashing of a political and cultural crisis that would correspond to the aspects related to the purpose of existence of these organizations, to the distance of the activist stamp and would be aggravated by the loss of the political character And isonomic in favor of the predominance of technical-instrumental thinking. This is not only due to the coexistence of the utilitarian and substantive aspects of rationality, but rather by a certain relation of predominance of those in relation to them. This theme has already been explored by other authors who have been based on the work developed by Maurício Serva (1996), many of whom have pointed to "third sector" organizations as an appropriate locus for the investigation of substantive reason. Currently, such research has advanced and is in the second stage, which consists in the investigation of specific aspects of management and relationship between members of the organizations. In this context, this work is located, which sought to analyze the manifestations of the aspects of reason in the organizational environment from three of the eleven categories proposed by the study of Serva (1996): Reflection on the organization; Organizational values and objectives; Communication and interpersonal relationships. In view of this understanding and through a study carried out in a Brazilian Non - Governmental Organization (Instituto Terra - Aimorés / MG), it was intended to understand, from the discursive practices concerning the workers' daily life, the manifestation of formal rationality , Imposed by the logic of capital to organizations, and isonomic goals. Thus, the research problem was the following: How are the elements of instrumental and substantive rationality invested in the practical and discursive interrelationships within the management and daily life of the workers of the Non-Governmental Organization Instituto Terra? The interpretative nods present in this research start from the analysis of Discourse of the French School (AD) where the contributions of Pecheaux (1988), Orlandi (2007) and Bakhtin (2008; 1999) on the Conditions of Production, Polyphony and Interdiscursivity. As main results it was verified that the context of the organization under study configures a dynamic space of tension in function of different pressure mechanisms that favor instrumental and substantive aspects of rationality. The founding ideology is the main substantive element that permeates the speeches of the interviewees and collides with the instrumentality of the discourse of efficient management sustained and naturalized in the speeches